An expeditious method for the ultra-level chemosensing of uranyl ions. Issue 8 (13th February 2020) - Halali, Vishaka V.; Balakrishna, R. Geetha
Abstract : In this study, a new colorimetric chemosensor based on intramolecular charge transfer was designed for the qualitative and quantitative detection of uranyl ions at trace concentrations in environmental water samples. Abstract : In this study, a new colorimetric chemosensor based on intramolecular charge transfer was designed for the qualitative and quantitative detection of uranyl ions at trace concentrations in environmental water samples. The probe exhibited color change from colorless to red upon binding with uranyl ions at physiological pH. This color change offered a simple, rapid and reliable method for the selective and sensitive visual detection of trace levels of uranyl (UO2 2+ ) ions without any need for sophisticated instruments. The detection limit of the synthesized chemosensor for uranyl ions was found to be 1.9 nM. This method was successfully applied to detect trace amounts of uranyl ions in various groundwater samples. Moreover, immobilized paper strips developed using this sensor have been demonstrated for the naked eye or on-field detection of UO2 2+ ions.